KINERJA KEUANGAN YANG DIMEDIASI CORPORATE SOCIAL RESPONSIBILITY (CSR) (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2017-2019) - Mohklas, Mohklas; Pancawardani, Nurul Latifah (JAB (Jurnal Akuntansi & Bisnis), 2021)
This study aims to analyze the effect of environmental performance and company size on financial performance with Corporate Social Responsibility (CSR) as an intervening variable in manufacturing companies listed on the Indonesia Stock Exchange. In this study, environmental performance is measured by PROPER and company size is measured by total assets. Population in this study are manufacturing companies listed on the Indonesia Stock Exchange 2017-2019. The sample was selected using a positive sampling method by producing 21 manufacturing company data, so that the number of research data for 3 years was 63 samples. Data analysis technique used is multiple linear regression analysis and path analysis. Results of hypothesis testing and path analysis, it can be concluded as follows: environmental performance has an effect on corporate social responsibility, company size has no effect on corporate social responsibility, environmental performance has no effect on financial performance, while firm size has an effect on financial performance. Direct effect of environmental performance on financial performance is 0.131, indirectly it is 0.261 through Corporate Social Responsibility, the total effect is 0.392. Company size has a direct effect of -0.277, 0.077 indirectly through Corporate Social Responsibility, the total influence is -0.200. Corporate Social Responsibility variable in this study can serve as a mediation for the relationship between environmental performance and company size on financial performance, this is because the value of the indirect effect is greater than the direct effect.Keywords: Financial Performance, Environmental Performance, Company Size, Corporate Social Responsibility